2. tüüpi diabeedi Eesti ravijuhend 2016 - Ambos, Anu; Raie, Evelin; Kiudma, Tarvo; Reppo, Ingrid; Rätsep, Anneli; Tammiksaar, Kaia; Toomsoo, Tatjana; Volke, Vallo (Eesti Arst, 2016)
Eesti Arst 2016; 95(7):465–473